Pengaruh Penggunaan Media Kartu terhadap Kemampuan Membaca Siswa Kelas I SDN 10 Lubuk Buaya Padang - Arief, Darnis (Institut Agama Islam Negeri Imam Bonjol Padang, 2014)
Reading is one of the most important language skills in the Elementary School since it is a tool to learn other subjects.Â It is so because whatever you learn, you will need reading skills.Â However, several researches show that Elementary school studentsâ reading competence were still low.Â Therefore, the current research problem is addressed to answer the question: âIs there any impact of using cards to studentsâ reading skill at Elementary School?âÂ In line with the question, then, the study aims at investigating the impact of cards to first grade studentsâ reading skills in the Elementary School.Â As a quasi experimental research, the datum was collected through reading test.Â The reliability of instrument was tested through split method, while content validity was applied to the whole content.Â With the t-test, the research shows that the use of Cards gave significant impact to studentsâ reading skill in the Elementary School.Â Therefore, it is fair to suggest that teachers at Elementary school should use cards to teach students in early reading activity.CopyrightÂ Â©Â 2014Â by Al-TalimÂ AllÂ rightÂ reservedDOI:Â 10.15548/jt.v21i1.68